Understanding Psychological Safety in Hybrid Work Teams: Experiences of Barriers and Facilitators - Nilsson,Lovisa; Norström,Wilma (2024)
This study aims to enhance understanding of the barriers and facilitators to creating and maintaining psychological safety in a hybrid work environment. It also explores whether these factors differ for hybrid teams compared to traditional settings. The research involved a literature review of existing barriers and facilitators, followed by qualitative, semi-structured interviews with members of two hybrid organisational work teams. These interviews allowed for the identification of hybrid-specific barriers and facilitators. Participants also conducted self-assessments of their psychological safety, with both teams demonstrating high levels of psychological safety. Key hybrid-specific barriers identified include loss of informal conversations, loneliness, varying locations, and lack of body language. Hybrid-specific facilitators include established on-site relationships and prior experience. The study concludes that inclusive leadership, leader humility, and strong work relationships are essential facilitators of psychological safety in any setting, not just for hybrid work settings. Facilitators such as active listening, leader transparency, and social capital, while crucial, are less visible in hybrid environments due to the remote nature of work. Moreover, hybrid teams with high psychological safety rarely face barriers such as abusive supervision and job insecurity, and issues like enforced leadership decisions and being monitoring are not significant in these contexts. Furthermore, managers in hybrid teams with high psychological safety can use these insights to refine their leadership by implementing structured team interactions, ensuring decision-making transparency, and creating safe spaces for team members to express concerns. These practices can enhance team cohesion, creativity, and performance, leading to more resilient and adaptive teams. Organisations can benchmark their practices against these findings to assess and improve psychological safety.
Keywords: Psychological safety; Hybrid work; Hybrid work environment; Hybrid team; Team psychological safety; Barriers; Facilitators